Atmospheric Interpretation in Islamic and Physics Perpective - Jihan Ariqatur Rafiah; Firdausita Safitri Rakhmah; Winarti (Proceeding International Conference on Religion, Science and Education, 2023)
The atmosphere is a layer of gas that surrounds a planet, including the earth. The function of the atmosphere is to protect the earth from exposure to ultraviolet radiation which can harm the life of living things on earth with the ozone layer. The atmosphere in the Qur’an can be associated as sky or sama’, this is explained in the Qur’an of Al-Baqarah verse 29. The purpose of this research is determined the relationship between the atmosphere by perspective of Islam and Physics. The research’s method used descriptive qualitative is using literature study. The results of this research to show that the layers of the atmosphere, when viewed from the perspective of the Qur’an, very beneficial functions for life on earth, including the layers of the atmosphere as a place for the process of rain formation and places that have different oxygen composition properties in each layer. In addition, the atmosphere is the place where lightning and lightning occur before the rain occurs, as a source of disaster for the unjust and the atmosphere is a source of sustenance and blessings. Meanwhile, based on a physics perspective, the layers of the atmosphere have different functions based on the characteristics of the gas content and pressure in each layer of the atmosphere.